Oncologic Results of Supracricoid Laryngectomy: Results From Two Tertitory Centers - ENVER, NECATİ; YUMUŞAKHUYLU, ALİ CEMAL; OYSU, ÇAĞATAY (My University, 2020)
INTRODUCTION: Larynx cancer is the second most frequent head and neck cancer and important cause of morbiditity and mortality. Supracricoid laryngectomy is one of the open partial laryngeal surgerical techniques which is an important tool for treatment of laryngeal cancer. The purpose of this study was to evaluate the oncological outcomes of laryngeal carcinoma patients treated with supracricoid laryngectomy. METHODS: A total of 47 cases were retrospectively analyzed from two tertiarian head and neck clinics with laryngeal carcinoma that underwent supracricoid laryngectomy from 2009 to 2019. Sociodemographic characteristics, histopathologic characteristics of tumor specimens, and survival analysis were assessed. RESULTS: Early stage laryngeal cancer was detected in 29 (61.7%) of the patients, and 20 (38.3%) of the patients had advanced laryngeal cancer. In 29 cases (61.7%) larynx cancer was located in glottis and lymph node involvement was found to be significantly less in cases with glottic location (p< 0.001). While 5-year overall survival was 74.5%, 5-year overall survival was 88.5% and 69.2% in early and advanced stage cases. DISCUSSION AND CONCLUSION: The two most important factors in the determination of successful treatment in treating laryngeal cancer are survival time and preserving laryngeal function. Supracricoid laryngectomy is one of the key tools used in treating laryngeal cancers. Through preserving a healthy larynx in appropriate patients, it is possible to provide permanent improvement while adhering to the surgical technique and oncological rules.

GİRİŞ ve AMAÇ: Larenks kanseri tüm baş boyun kanserleri arasında en sık görülen ikinci kanserdir ve önemli bir morbidite ve mortalite nedenidir. Suprakrikoid larenjektomi cerrahisi, larenks fonksiyonlarının mümkün olduğunca korunmasına imkân veren etkili bir tedavi yöntemidir. Çalışmamızda kliniğimizde son 10 yıl içinde yapılan açık parsiyel larenks cerrahi vakalarının histopatolojik parametrelerini ve onkolojik sonuçlarını paylaşacağız. YÖNTEM ve GEREÇLER: Ocak 2009 ve Temmuz 2019 arasında kliniğimizde histopatolojik olarak larenks yassı hücreli karsinom tanısı almış ve suprakrikoid larenjektomi cerrahisi uygulanmış 47 hastanın verileri retrospektif olarak incelendi. Hastaların sosyodemografik özellikleri, tümör spesmenlerinin histopatolojik özellikleri ve sağkalım analizleri değerlendirmeye alındı. BULGULAR: Hastaların 29’unda (%61.7) erken evre larenks kanseri saptanmış olup, 18’inde (%38.3) ileri evre larenks kanseri mevcuttur. Larenks kanser 29 olguda (%61.7) glottik yerleşimli olup lenf nodu tutulumu glottik yerleşimli olgularda anlamlı derecede daha az olarak saptanmıştır (p< 0.001). 5-yıllık genel sağkalım %74.5 olarak saptanmışken, erken ve ileri evre olgularda 5-yıllık genel sağkalım %88.5 ve %69.2 olarak saptanmıştır. TARTIŞMA ve SONUÇ: Larenks kanseri tedavisinde tedavi başarısının değerlendirilmesinde en önemli iki ölçüt sağ kalım süresi ve organ fonksiyonun devamlılığıdır. Larenks kanserlerinin tedavisinde suprakrikoid larenjektomi önemli araçlardan biridir. Cerrahi teknik ve onkolojik kurallara bağlı kalındığında uygun hastalarda fonksiyonel bir larenksi koruyarak hastalarda kalıcı iyileşme sağlamak mümkündür
Larenks Kanseri tedavisinde SKL Cerrahisi ve Onkolojik Sonuçları: 3.Basamak İki Merkezden Sonuçlar
Keywords: Laryngeal Neoplasms; Laryngeal Neoplasms/surgery; Survival Analysis; Larenks Neoplasmlari; Larenks Neoplazmlari/Cerrahi; Sağ kalım analizi